2019
DOI: 10.4236/msce.2019.71003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Coating Corrosion Inhibitor on Protection of Reinforced Mortar

Abstract: Corrosion of reinforced concrete is the most important cause of concrete structure deterioration. In the present study, the protective effect of the reinforcement mortars against corrosion is examined. In particular, the chloride penetration resistance on reinforced cement mortars using organic coating as additive containing was studied. The aforementioned additive consists of corrosion inhibitor for protection of steel rebars against pitting corrosion. For the experimental procedure, four (4) different types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Also, in a previous work [19] where it was examined the use of the same organic coating containing corrosion inhibitor that was used at the present study, in order to estimate anticorrosion protection on the reinforcement steel, showed that the use of the system organic coating/corrosion inhibitor applied on the surface of the mortar and on the surface of the steel rebar appeared an optimum anticorrosion protection of 29% based on mass loss, after 24 months in the corrosive environment, while the system organic coating/corrosion inhibitor applied on the surface of the mortar only gave a protection degree of 11% based on mass loss for the same period.…”
Section: Discussionmentioning
confidence: 78%
“…Also, in a previous work [19] where it was examined the use of the same organic coating containing corrosion inhibitor that was used at the present study, in order to estimate anticorrosion protection on the reinforcement steel, showed that the use of the system organic coating/corrosion inhibitor applied on the surface of the mortar and on the surface of the steel rebar appeared an optimum anticorrosion protection of 29% based on mass loss, after 24 months in the corrosive environment, while the system organic coating/corrosion inhibitor applied on the surface of the mortar only gave a protection degree of 11% based on mass loss for the same period.…”
Section: Discussionmentioning
confidence: 78%